BS EN IEC 60794-1-303. Optical fibre cables. Part 1-303. Generic specification. Basic optical cable test procedures. Cable element test methods. Ribbon dimensions. Aperture gauge, Method G3 (3rd December 2021) - British Standards Institution,
No abstract available